Ultrasound-Guided Needle Biopsy for Diagnosis of Advanced-Stage Malignancies of the Upper Aerodigestive Tract. Issue 1 (February 2017) - Smith, Aaron; Grady, Anthony; Vieira, Francisco; Sebelik, Merry
Objective: Traditionally, direct laryngoscopy confirms stage and tissue diagnosis prior to treatment planning. Patients who are frail or have tenuous airway anatomy may incur risks while undergoing anesthesia. Further, direct laryngoscopy is scheduled after initial examination, introducing diagnosis delay. This study investigates the impact of ultrasound examination with guided needle biopsy compared with traditional operative biopsy. Study Design: Case series. Setting: Tertiary head and neck clinic. Subjects and Methods: The records of patients at the Veterans Affairs Medical Center Memphis and Regional One Health who had supraglottic, oropharyngeal, and hypopharyngeal cancer that was diagnosed by ultrasound needle biopsy were reviewed from 2011 to 2016. Demographics, stage, biopsy results, and treatment were abstracted. Results: Seventeen patients who underwent ultrasound-guided needle biopsy of the primary site were included. Average age was 63 years old, and 65% of patients were stage T4 (11/17). Needle biopsy yielded malignant cells in 76% (13/17). Eleven patients were included in subsequent analysis because 6 patients underwent needle biopsy only. Fisher exact test showed no difference between the 2 methods ( P = .27). Sensitivity was 86% and specificity was 100%. Seven patients had a median potential delay in diagnosis of 10 days. Conclusions: Ultrasound can be used effectively to obtain a tissue diagnosis, circumventing an operative biopsy. Moreover, ultrasound may provide additional imaging details to support accurate staging. This strategy may prove worthwhile to cut costs and reduce delay to staging, reduce risk for those with contraindications to anesthesia, and increase staging accuracy via enhanced imaging details.